Strategi Diplomasi Indonesia dalam Presidensi G-20 di Bali - Lian Mutiara Timur, Rio Sundari (UIR Press, 2023)
This study discusses Indonesia's diplomatic strategy in implementing the G-20 Presidency. In this research the author uses the concept of Diplomacy, which is the art of building relationships with other parties or countries that can improve and strengthen relations between countries. The Group of Twenty (G-20) is a multilateral cooperation forum consisting of developed and developing countries, which was formed to find solutions to the global financial crisis and discuss general problems and national security needed to prevent future crises. Developed countries can learn how to see and treat developing countries as equal global cooperation partners as a result of the economic and political role that Indonesia currently plays. Indonesia's G-20 Presidency has tried to overcome various new problems during its one year leadership. Indonesia has reached its peak by producing a document called the Bali G-20 Leaders' Declaration. The author uses qualitative research which aims to increase understanding of the phenomena that occur because the subject and object are considered as a constant and dynamic unit. The author uses secondary data sources which are a collection of data and information that has been collected from previous research, such as books, journals, documents and other library data sources.